Speech and singing performance in patients suffering a cerebellar stroke: a case study - Sandoval Zúñiga, María Soledad; Henríquez Espejo, Carolina; Henríquez Navarrete, Liza; Elissalde Reyes, Andrea; Rodríguez Rivas, Diego (Revista de Investigación en Logopedia, 2020)
The objective of this study was to characterize speech and singing performances of two subjects who suffered ataxic dysarthria due to a cerebellar stroke for describing their results according their clinical and sociodemographic characteristics.This study was of quantitative type, with a non-experimental-transversal design with a descriptive scope. Both patients suffered a cerebellar stroke but they differed in the characteristics of dysarthria, vocal technique, age, and rehabilitation frequency, between others factors. The instruments that were used to measure varibales corresponding to: Protocolo de Evaluación de Habla (González y Toledo, 2002), Protocolo de Habla versus Canto para pacientes disártricos, the Voice Handicap Index (VHI) by Núñez-Batalla et al. (2007) and the RASATI scale (Pinho and Pontes, 2002).The results indicated that who suffers a mild dysarthria has better speech and singing results compared to the subject who suffers from a moderate dysarthria due to the differences that they posse like pathology severity, neurological characteristic, therapy frequency, age and vocal technique before the vascular event.Both subjects showed alterations in basic motor processes in respiration, phonation and prosody.
Keywords: speech; singing; ataxic dysarthria; vocal technique; cerebellar stroke